The Pocong Oath as a Socio-Legal Mechanism of Conflict Resolution among Madurese Muslims (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
This study explores the function of the pocong oath within the Madurese Muslim community through a socio-legal approach, focusing on its legal validity and its capacity to contain social conflict. Data were collected through semi-structured interviews with six informants—religious leaders, oath practitioners, and community members—in Singosari District, Malang Regency. Using thematic coding, the analysis examined the social meanings, legitimacy, and effectiveness of the practice. The findings show that the pocong oath serves as an informal dispute resolution mechanism when formal legal avenues reach a deadlock, particularly in cases of accusations lacking strong evidence, such as witchcraft, theft, or adultery. Socio-culturally, the oath carries moral and symbolic weight that helps defuse potential conflicts and preserves both individual honor and community cohesion. These results demonstrate that legal practice is shaped not only by codified norms but also by cultural, religious, and local values. The study contributes to the discourse on legal pluralism and advances understanding of tradition-based justice mechanisms in Islamic law and conflict resolution